Litter Proouction and Release of Nutrients in Coniferous Forests of Himachal Pradesh - Singh, R. P.; Mathur, H. N.; Gupta, M. K. (Indian Forester, 1984)
The present investigation deals with the litter production and nutrient tnrnover in four prominent coniferous species viz. Abies pindrow; Piceo smithiana; Cedrus deodara and Pinus wallichiano of Himachal Pradesh. Annual litter production and the amounts of nutrients released annually through litter fall bave been worked out in all the four species. A comparative account of nutrients released anually through litter fall lu different species is also prepared.